KAJIAN KUALITAS UDARA KOTA SAMARINDA DITINJAU DARI ASPEK AKTIVITAS KENDARAAN BERMOTOR - Bohari Yusuf (PROSIDING SEMINAR KIMIA, 2014)
Declining air quality and increasing number of vehicles at Samarinda City indicating that there is strong relationship between both. Research was done to understand current air pollution level in Samarida as ISPU Criteria and relationship air pollutant level with number of vehicles activities. Research was done by counting number of vehicles and collecting air samples at five crowded traffic intersection. Air samples tested in laboratory for ISPU specified air pollutant level, which are CO, NO2, SO2, O3 and dust (PM 10). Analysis of correlation was conducted to understand relationship between numbers of vehiclesand air pollutant level. Average level of air pollutant and their ISPU value were CO 2803ug/m3 (28.03; Good), NO2 47.9ug/m3 (-; Good), SO2 53.0ug/m3 (33.12; Good), O3 31.3ug/m3 (13.04; Good) and Dust 36.1ug/m3 (36.1; Good). There was positive correlation between numbers of vehicles and air pollutant level with coefficient >0.9. Therefore, limit numbers of vehicles before limit air pollutant level passed could be predicted. Prediction of limit numbers of vehicles based on CO level were 31217 units, NO2 level were 54186 units, SO2 level were127692 units, O3 level were 48672 units and dust level were 26371 units. Levels of CO, NO2, SO2, O3 and dust (PM 10) at Samarinda City still comply PP No. 41 year 1999 with Good as ISPU criteria average. Increase in number of vehicle will increase air pollutant levels too.Keywords: Air, Level, Pollutant, ISPU, Quality